Identification of Susceptibility Loci for Scoliosis in FIS Families With Triple Curves - Marosy, Beth (2010)
The triple curve pattern (three lateral curvatures of equal severity) has been recognized as a distinct and unique clinical subtype of scoliosis. As part of a large study of familial idiopathic scoliosis (FIS), a subset of five families with a triple curve pattern (at least one member of each family having a triple curve) was evaluated to determine if this curve pattern was linked to any of the markers previously genotyped as part of the STRP-based previous linkage screen. Model independent linkage analysis (SIBPAL, v4.5) of the initial genomic screen identified candidate regions on chromosomes 6 and 10 when FIS was analyzed both as qualitative and quantitative traits in single- and multipoint linkage analyses. Additional fine mapping analyses of this subgroup with SNPs corroborated the findings in these regions (P <0.001). These regions have been previously linked to FIS, however, this is the first time these regions have been implicated in a clinically well-defined subgroup and may suggest a unique genetic etiology for the formation of a triple curve.